Transphobic Assaults Experienced by Felix Love in Felix Ever After by Kacen Callender - Asmarani, Ratna; Rini, Cristyvilda Priskila (Proceedings International Conference of Culture and Sustainable Development; Vol 3 (2025): PROCEEDINGS ICOCAS, 2025)
Gender transition which happens more and more today can serve as an outlet to escape from the strictness of gender binary. However, gender transition faces inevitable consequences as experienced by Felix Love, the main character in Kacen Callenderâ€™s novel entitled Felix Ever After.Â  Even though he has declared or coming out as a transgay or a trans guy who like males instead of females, he still has to encounter several assaults done by transphobic people. To analyze the problem, several concepts are used, such as, the concept on gender transition, deadnaming, and transphobia. The methods applied are library research method, close reading technique, qualitative research method, and contextual research method. The result shows that transphobic assaults produce devastating effects for the gender transitioning person. However, the supports from friends and support group bring out the tenacity of Felix Love. Finally, he can overcome the transphobic assaults, even he can punish the assailant in his own way and continue his life. The multifaceted transphobic assaults open other discussions on novels with transgender theme.
Keywords: transgay, transphobic, deadnaming, Felix Ever After